The Route of Paul's First Journey to Pisidian Antioch - Wilson, Mark W. (New Testament studies, 2009)
The route of Paul's first journey between Perga and Pisidian Antioch is still disputed. This article examines the three alternatives proposed by scholars. It explores the geographical and historical evidence for each route, looking especially at the extensive road system that existed in Pamphylia, Pisidia, and south Galatia in the first century. Bible atlases routinely depict one route and the reasons for this choice are discussed. Based on a review of the evidence, a fresh hypothesis for the route of the first journey is suggested.